The development of talent in adults : a thesis presented in partial fulfillment of the requirements for the degree of Masters in Education at Massey University - Redwood, David John (The Author, 1999)
Giftedness and talent in children has been a significant area of research and endeavour in education over nearly a century and there is a large body of literature on the subject available to researchers. However this is not the case for adult talent and the actual process of talent development in adults has not been explored in any depth, indeed it has been ignored to a certain extent in academic research. Additionally it seems to be assumed that the process of talent development in adults is the same or very similar to that in children. One of the central foci of this study is the proposition that talent development in adults does not follow the same process as that in children, indeed in many aspects it is quite different. Adults are not merely older children who perceive, judge and act in the same ways that children do and so why would they develop talent in the same way or for the same reasons that children do? The question is also asked as to whether an adult would have to be gifted in order to develop talent? In this study the life paths of a small group of talented individuals were investigated and major causal and a-causal influences identified in their histories. A form of enquiry was developed that focused on synthesising the various influences so as to interpret the process of talent development. This was termed Critical Life Path analysis and by using quantum and systems notions a description of life path processes was attempted. The Critical Life Path is viewed as a holistic, interconnected process in which the outcomes are determined by the combinative effects of critical influences identified by the participants and genetically based patterns of preference that resulted in timely and efficacious patterns of behaviour. These patterns of thinking and action enabled the individuals to increasingly construct supportive and special environments that were synchronous with their proposed inherited patterns of preference and to progress rapidly and effectively along unique paths of talent development.
Keywords: Gifted persons; Adulthood; Success